Optimasi Penjualan Warung Makan Solo Menggunakan Progam Linier dengan Metode Simpleks - Lestari, Natasya Dyahayu; Hamdi, Ahmadil; Saofitri, Saofitri; Alfian, Muhammad Rijal; Maharani, Andika Ellena Saufika Hakim (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Food stalls are one form of culinary business that faces challenges in managing limited raw materials to maximize profits. This study uses a linear programming method with a Simplex approach to optimize the profits of Solo food stalls that sell three main menus: fried rice, fried noodles, and meatballs. The optimization model is designed by considering the limitations of raw materials such as vegetables, eggs, chicken, oil, sauce, and spices, as well as the selling price and cost of raw materials per portion. In this case, we use manual and software analysis, namely by using POM-QM for Windows. The results of manual and software analysis show the same results, namely by producing 25 additional packages of fried rice and 33.33 packages of meatballs. Because the requested results use integer numbers, we perform branch and bound analysis to produce the maximum value with all values ????of x1, x2, x3 are decimal numbers. The optimization results show that the Simplex method can determine the combination of the number of portions of each menu optimally to achieve maximum profit without violating resource constraints. Thus, this article was created so that we can determine the maximum profit with the availability of existing raw materials and with the capacity that traders have to make it easier for traders to manage.